2009
DOI: 10.1136/jcp.2008.063859
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and i-NOS expression are prognostic factors in serous epithelial ovarian carcinomas after complete surgical resection

Abstract: VEGF-A and i-NOS are prognostic markers for clinical outcome in serous ovarian cancer patients with macroscopic complete tumour resection (R0). Hence, pre-therapeutic assessment of VEGF-A as predictive factor for an antiangiogenic therapy might be of clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…19 Improved progression-free survival has been described in patients with iNOS-negative ovarian tumors. [21][22][23] In our study, we found high iNOS expression in both type I and II tumors, but with a significantly higher frequency in the latter group. However, iNOS expression did not stand as an independent prognostic marker when other factors were analyzed.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofsupporting
confidence: 59%
“…19 Improved progression-free survival has been described in patients with iNOS-negative ovarian tumors. [21][22][23] In our study, we found high iNOS expression in both type I and II tumors, but with a significantly higher frequency in the latter group. However, iNOS expression did not stand as an independent prognostic marker when other factors were analyzed.…”
Section: Recently Kurman Et Al Proposed a New Classification Ofsupporting
confidence: 59%
“…Others have reported that the elevated expression of VEGF in the tumour of EOC patients is associated with poor prognosis [21,26,28,29]. Whilst VEGF has been shown to be a prognostic factor in EOC, this study adds to the field by correlating VEGF status specifically with platinum treatment response.…”
Section: Discussionmentioning
confidence: 86%
“…8 The amount of VEGF-A expressed by tumor cells correlates with poor prognosis in many types of tumors including lung, gastric, colon, prostate, ovary and melanoma. [9][10][11][12][13][14] Of the 3 closely related members of the VEGFR family (VEGFR1, 2, 3), VEGFR2 (also named as KDR or Flk1) and VEGFR3 mainly expressed in vascular and lymphatic endothelial cells, plays major roles in VEGF-A and VEGF-C induced angiogenesis and lymphangiogenesis. 15,16 Binding VEGF ligands to the extracellular domain of VEGFRs on the cell surface of the endothelial cells leads to dimerization of the receptor, and consequently, phosphorylation of the intracellular kinase domain of VEGFRs and triggers activation of downstream cell signaling cascades, including PI3K/AKT, PKC, Raf/Ras and ERK pathways, resulting in vascular/lymphatic endothelial cell proliferation and formation of new vessel branches.…”
Section: Introductionmentioning
confidence: 99%